Enhancing Islamic Education with Multicultural Perspective Through Surah Al-’Ankabut - Yanti, Yanti; Hayani, Aida; Salim, Ahmad; Assalihee, Muhammadafeefee; Nik Abdullah, Nik Md Saiful Azizi (Multicultural Islamic Education Review, 2024)
This research aims to obtain a comprehensive understanding of Islamic education with a multicultural perspective through Surah Al-’Ankabut (29:46). The methodology employed is a library research type, wherein the researcher collects, analyzes, and presents theoretical data from various literary sources such as books, journals, and articles relevant to the research focus. Relevant data is gathered from scholarly writings, magazines, and other sources related to the focus of the writing and discussion. The data analysis technique utilizes a critically descriptive content analysis method to examine and describe relevant data critically. The primary finding of this research underscores the significance of utilizing Surah Al-’Ankabut (29:46) as a source of Islamic education that enriches multicultural perspectives, enabling a broader and more inclusive understanding of religious values within the context of culturally diverse societies. The novelty of this research lies in the integration of Islamic education and multicultural perspectives through a critical analysis of the Qur'anic text, offering a new contribution to contemporary Islamic educational thought. Thus, this research elaborates in detail on how Surah Al-’Ankabut (29:46) can be utilized as a means to enhance the understanding and teaching of Islamic education while considering cultural diversity in society.